Fire performance analysis for buildings - Fitzgerald, Robert W.; Meacham, Brian J. (Wiley, 2017)
Fire Performance Analysis for Buildings, 2nd Edition has been completely restructured around a performance based framework. Applications integrate traditional fire defenses with fire science and engineering to combine component performance with holistic performance.